The relationship of work environment factors toward job satisfaction in Telekom Malaysia Berhad (TM) Kedah/Perlis / Nurul Akmar Mohamad - Mohamad, Nurul Akmar (2013)
The aim of this study is to measure the relationship of work environment factors toward job satisfaction among employees in the private sector. Also, it is to know whether work environment factors may result in low or high job satisfaction among those employees. This study compresses on the factors of work environment such as supervision, nature of work, and recognition. The item being used, measures, and other methods used to determine the sample size were stated in this section. For this research, 80 questionnaires were distributed to the employees as the respondents in the company. The respondents are ranged in between 18-50 years old and above. The respondents are among managers and supporting staffs.From the results in findings, those work environments factors do give impact on employees' job satisfaction. Also, there is a positive relationship between work environment factors toward job satisfaction among employees in the company .In summary, the nature of work has strongest relationship or contributed the most toward job satisfaction. The employees in the company feel that their self-motivation itself contributed to the job satisfaction. Also, it is important to identify the areas of workers' concern in order to make any improvement need to ensure their job satisfaction.